2007
DOI: 10.1002/chir.20381
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective degradation of fungicide benalaxyl in soils and cucumber plants

Abstract: The enantioselective degradation of benalaxyl has been investigated to elucidate its behavior in several agricultural soils and plants (cucumber). Racemic benalaxyl was fortified into five types of agricultural soils and sprayed leaves of cucumber plants, respectively. The degradation kinetics and the enantiomer fraction (EF) were determined by normal-phase high-performance liquid chromatography (HPLC) with diode array detection (DAD) on the chiral column filled cellulose-tri-(3,5-dimethylphenylcarbamate)-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 18 publications
1
60
0
Order By: Relevance
“…Biodegradation in plants and vegetables showed faster degradation of (S)-benalaxyl in diverse experimental conditions, while experiments in soil reported preferential degradation of (R)-benalaxyl [134,135]. (S)-benalaxyl exhibited somewhat smaller half-life values in freshwater algae cultures and in the same study enrichment of the (R)-enantiomer was also reported [136].…”
Section: Biodegradation Studies Of Chiral Pesticidesmentioning
confidence: 71%
See 2 more Smart Citations
“…Biodegradation in plants and vegetables showed faster degradation of (S)-benalaxyl in diverse experimental conditions, while experiments in soil reported preferential degradation of (R)-benalaxyl [134,135]. (S)-benalaxyl exhibited somewhat smaller half-life values in freshwater algae cultures and in the same study enrichment of the (R)-enantiomer was also reported [136].…”
Section: Biodegradation Studies Of Chiral Pesticidesmentioning
confidence: 71%
“…Dissipation studies and field-only experiments with no incubation experiments considered were left out [72,149,[156][157][158][159][160][161][162][163][164][165][166][167]. beta-cypermethrin soil laboratory incubation experiments under sterile and non-sterile conditions HPLC-VWD enantioselective degradation of beta-cypermethrin observed; different degradation rates observed for the four beta-cypermethrin isomers; EF variation noticed during the degradation process [143] beta-cypermethrinsoil laboratory incubation experiments under sterile and non-sterile conditions with acidic and alkaline matrices, and with racemic mixture and individual enantiomers HPLC-UV enantioselective degradation of racemic-beta-cypermethrin observed only in non-sterile soils; different degradation rates and half-lives observed for the four beta-cypermethrin isomers; no enantiomeric enrichment observed during degradation of individual enantiomers [144] Regarding the analytical methods used to quantify pesticides' enantiomers during biodegradation, the trend is clear and high-performance liquid chromatography with a diode array detector (HPLC-DAD) [117,122,123,126,128,134,135,140,152] and an ultraviolet detector (UV) [120,129,132,136,138,141,144,146,150,151,155], as well as liquid chromatography tandem-mass spectrometry (LC-MS/MS) [21,...…”
Section: Biodegradation Studies Of Chiral Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The (R)<(S) enantioselectivity in metabolism of aryloxyalkanoic acid herbicides was observed in some plant species including green algae, and similarly in soil metabolism, but with no enantiomerization. 82,[112][113][114][115] Similar enantioselectivity was observed for metalaxyl (10) 89,116) and benalaxyl (11), 91) with no enantiomerization of the former herbicide reported. The simple comparison of soil and plant metabolism may suggest less contribution of enzyme-mediated enantiomerization of these pesticides in plants.…”
Section: Plant Metabolismmentioning
confidence: 70%
“…3 (4)]. 86) The opposite enantioselectivity of degradation [(R)>(S)] was reported for acetoanilide herbicide metalaxyl (10) [88][89][90]93) and benalaxyl (11), 91,92) while the same enantioselectivity as aryloxyalkanoic acids was observed for the acid metabolite of metalaxyl (10).…”
Section: Microbial Degradation In Soilmentioning
confidence: 95%